PENANGGULANGAN GIZI BURUK PADA DOKTER DAN PETUGAS GIZI PUSKESMAS DI DINAS KESEHATAN KABUPATEN TANAH DATAR - Helmizar Helmizar; Susmiati Susmiati; Asrawati Nurdin; Hafifatul Auliya Rahmy; Restu Sakinah; Rani Wahyuni; Serly Suryana; Monika Trijuli Astuti; Meicy Astuti (LPPM Universitas Andalas, 2020)
Malnutrition is a nutritional problem determined based on anthropometric indicators of body weight according to height or body length (BW / TB) with a z-score of <-3 SD and the presence or absence of edema. There are many problems with malnutrition in poor and developing countries such as Indonesia. Based on the 2015 Indonesian Health Profile, as many as 26,518 toddlers suffer from malnutrition, with a prevalence of 3.8% malnutrition in Indonesia. The current management of nutrition problems cannot only be handled by the government but requires the involvement and support of other stakeholders, such as elements of higher education. This activity aims to increase the knowledge of doctors and officers who work in Puskesmas throughout Tanah Datar Regency in overcoming malnutrition. The method used is training (capacity building). The training was given to Puskesmas stakeholders on efforts to improve children's nutritional status through mothers under five classes, measuring the nutritional status of children attending posyandu, providing nutrition education for mothers under five through mothers under five classes, and monitoring nutritional and nutritional intake of children under five. The main targets in implementing this activity are doctors, nutrition officers, and MCH officers in all puskesmas in Tanah Datar District. This activity is expected to increase health workers' knowledge in overcoming stunting in the Tanah Datar district. There was an increase in health workers' knowledge with an average pre-test score of 8.9, increasing to 9.3 in the post-test. With this activity, it is hoped that it can reduce malnutrition and mortality in children starting from the Tanah Datar district's scope.